Synthesis of Mesoporous Nickel Using Electrodeposition Method - Latifah, Sri Mulyati; Vito, Mochammad Ghais; Prajitno, Djoko Hadi (Metalurgi, 2024)
Mesoporous material technology has recently become increasingly popular among scientists and industry professionals. Electrodeposition is a metal deposition process that employs an electric current. The most typical applications of electrodeposition are metal coating (electroplating) and the creation of porous materials. This study aimed to analyze the effects of current and nickel synthesis time on the formation of mesoporous nickel morphology using corn starch. The method for producing mesoporous nickel deposits uses an electrodeposition process using corn starch additives. The process of making mesoporous nickel varies at currents of 4, 5, and 6 A, holding times of 3, 4, and 5 hours, and additional weights of corn starch of 1, 2, and 3 g, with the weight of nickel deposits produced being 1.19, 1.3, and 1.9 g, with an increase in nickel deposits from currents of 4 to 6 A (holding time of 3 to 5 hours) of 0.71 g (59.66%). The smallest pore diameter of 112 nm was obtained using a current of 6 A, a holding time of 5 hours, with 3 g of corn starch. Characterization was carried out on the electrodeposition layer using XRD (x-ray diffraction) and SEM-EDS (scanning electron  icroscope-energy dispersive spectroscopy), where the results of the XRD analysis showed the presence of α-Ni, Ƴ-Fe, and Fe1Ni3 compounds, and the results of SEM-EDS showed porous Ni deposits with the highest Ni concentration above 80%. The bigger the current employed and the holding period in the electrodeposition process, the heavier the Ni deposit formed.